2020
DOI: 10.1159/000505147
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Patients with Pruritus and Insomnia Have Increased Risk of Death

Abstract: Background: Pruritus and insomnia are common disorders in hemodialysis (HD) patients, with a major clinical impact as they are associated with poor quality of life and increased mortality. Their coexistence and impact on survival in HD patients have rarely been investigated. Our aim is to investigate the survival of HD patients presenting either none, one, or both disorders and to compare certain features between these groups. Methods: After the inclusion/exclusion criteria, 170 patients treated by HD or onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…However, in contrast to what might be expected based on previous research about the effect of itching on clinical outcomes over time (e.g. mortality and hospitalizations) [ 5 , 8 , 27 , 28 ], this study showed no faster deterioration of HRQOL in patients with (persistent) itching during 2 years of follow-up. Future research should investigate these relationships using a longer follow-up period.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to what might be expected based on previous research about the effect of itching on clinical outcomes over time (e.g. mortality and hospitalizations) [ 5 , 8 , 27 , 28 ], this study showed no faster deterioration of HRQOL in patients with (persistent) itching during 2 years of follow-up. Future research should investigate these relationships using a longer follow-up period.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, several treatment trials showed that a reduced itching intensity may result in improved HRQOL scores and sleep quality [ 5 ]. Furthermore, the literature suggests that better management of itching and HRQOL might even result in improved clinical outcomes, such as mortality and hospitalizations [ 5 , 8 , 27 , 28 ]. The need for and potential benefits of a treatment for itching are thus evident.…”
Section: Discussionmentioning
confidence: 99%
“…Soleymanian et al found that pruritus was a significant predictor for insomnia [21]. Similarly, Orasan et al found that survival at 20 months was lower in patients with both pruritus and insomnia [22], while in another study low quality of sleep was found to be related to increased mortality in hemodialysis patients [23]. It can be assumed that uremic pruritus has a negative effect on the general health functioning of hemodialysis patients since it is associated with systemic inflammation and cardiovascular mortality [24].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate sleep quality and pruritus among HD patients and their relationship. It should be noted that a previous publication found that pruritus and poor sleep quality significantly affect survival in this population [23]. The current study contains important findings from a developing country regarding the commonness of pruritus in hemodialysis patients and its devastating effect on sleep.…”
Section: Discussionmentioning
confidence: 69%